Endovascular repair of ruptured thoracic aortic aneurysms is associated with high perioperative mortality and morbidity - Geisbüsch, Philipp; Kotelis, Drosos; Weber, Tim; Hyhlik-Dürr, Alexander; Böckler, Dittmar (Journal of vascular surgery, 2010)
PURPOSE: To analyze early and midterm results after endovascular treatment of ruptured thoracic aortic aneurysms (rTAA). - METHODS: Between January 1997 and January 2009, a total of 236 patients received thoracic aortic repair in our institution; 23 patients (14 men; median age, 75 years; range, 60-88 years) due to a ruptured thoracic aortic aneurysm (rTAA). Rupture was defined according to computed tomography angiography (CTA) criteria with definite sign for hemorrhage outside the aortic wall. Patients with symptomatic TAA but with normal CT scans were excluded. A retrospective analysis of these patients was performed. Median follow up was 28 months (range, 0.1-82.5 months) and included serial aortic imaging at discharge, six, and 12 months and annually thereafter. - RESULTS: Technical success rate was 87%. The overall in hospital mortality was 48% with predominantly (50%) cardiac complications. Neurological complications occurred in three patients, two patients suffered from a transient ischemic attack (TIA)/stroke, and one patient experienced paraplegia after early conversion to open surgery. Primary endoleaks were seen in four of 25 patients (16%); no secondary endoleak was observed. Early conversion was necessary in two patients caused by an aortoesophageal fistula. The one- and three-year survival rates were 37.3% and 29.9% with no aortic or procedure-related death during follow up. Reintervention was necessary in four of 25 patients (16%). Cox regression analysis revealed preoperative renal insufficiency (hazard ratio [HR] 5.85, P = .0073) as an independent predictor of perioperative death. - CONCLUSIONS: The endovascular treatment of ruptured thoracic aortic aneurysms is associated with a high perioperative mortality and morbidity as well as poor midterm survival. Renal insufficiency proved to be an independent risk factor for perioperative death.